2014
DOI: 10.4097/kjae.2014.67.4.252
|View full text |Cite
|
Sign up to set email alerts
|

The effects of intravenous dexmedetomidine on spinal anesthesia: comparision of different dose of dexmedetomidine

Abstract: BackgroundIn this prospective, randomized, double-blind, placebo-controlled trial, we tried to find out appropriate amounts of single-dose dexmedetomidine to prolong the duration of spinal anesthesia in a clinical setting.MethodsSixty patients who were scheduled for unilateral lower limb surgery under spinal anesthesia were randomized into three groups receiving normal saline (control group, n = 20) or 0.5 or 1.0 ug/kg dexmedetomidine (D-0.5 group, n = 20; D-1, n = 20) intravenously prior to spinal anesthesia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 18 publications
(38 reference statements)
6
53
2
Order By: Relevance
“…Some studies have reported higher level of sensory-motor blockade of hyperbaric bupivacaine by the use intravenous dexmedetomidine [30,31,33,35,43] whereas, in study using low dose intravenous dexmedetomidine as sedative agent after spinal anaesthesia reported no difference in block characteristic by dexmedetomidine [36]. Lee et al [12] using two different dose of dexmedetomidine (0.5 mcg/kg Vs 1 mcg/kg) reported higher level of sensory block in both group of dexmedetomidine in comparison to placebo. Abdallah et al [27] did quantitative analysis in a meta-analysis after collecting data from the studies showing higher sensory block, but they failed to see any statistically significant increase in height of block by use of dexmedetomidine.…”
Section: Block Heightmentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies have reported higher level of sensory-motor blockade of hyperbaric bupivacaine by the use intravenous dexmedetomidine [30,31,33,35,43] whereas, in study using low dose intravenous dexmedetomidine as sedative agent after spinal anaesthesia reported no difference in block characteristic by dexmedetomidine [36]. Lee et al [12] using two different dose of dexmedetomidine (0.5 mcg/kg Vs 1 mcg/kg) reported higher level of sensory block in both group of dexmedetomidine in comparison to placebo. Abdallah et al [27] did quantitative analysis in a meta-analysis after collecting data from the studies showing higher sensory block, but they failed to see any statistically significant increase in height of block by use of dexmedetomidine.…”
Section: Block Heightmentioning
confidence: 99%
“…The timing and dosing method of intravenous dexmedetomidine in spinal anaesthesia varies in different study. Commonly used method of intravenous dexmedetomidine is either as loading dose just before or after spinal anaesthesia [12,[27][28][29][30][31][32], loading dose followed by continuous infusion [11,[33][34][35][36]. Most commonly used loading dose is 0.5 mcg/kg to 1 mcg/kg over 10 min and infusion dose range from 0.2 mcg/kg/hr to 1 mcg/kg/hr [25,26].…”
Section: Intravenous Dexmedetomidine and Spinal Anaesthesiamentioning
confidence: 99%
See 3 more Smart Citations